Neuropsychological correlates of reduced self-awareness of functional competency in persons with subjective memory complaints, mild cognitive impairment, and early probable Alzheimer’s dementia - Coddaire, Katie; McElvogue, Molly; Stokes, Ashley M.; Prigatano, George P. (Frontiers in Neurology, 2025)
Older adults with subjective memory complaints (SMC) often underestimate their cognitive and related functional competencies, while patients with mild cognitive impairment (MCI) or early probable Alzheimer’s disease dementia (AD) often overestimate their cognitive and functional abilities. We predicted that both cognitive (i.e., executive and memory) and non-cognitive (i.e., affective and motor) test performance of patients would be associated with reduced awareness of their functional limitations. Ten participants with SMC, 16 with MCI, and 10 with probable early AD were compared on measures of self and relatives’ perceptions of their daily functional capacities. Reduced self-awareness was behaviorally assessed by subtracting the patient’s subjective ratings of their functional abilities from the relatives’ (or significant others’) ratings of their functional abilities. Reduced self-awareness of functional competencies correlated with measures of language and calculation skills, memory, affect perception and expression, finger tapping movements, and overall cognitive status. The tendency to overestimate functional competences was associated with greater cognitive, affective, and motor impairments.